2016
DOI: 10.1111/cdev.12590
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Constrains Causal Learning in Childhood

Abstract: Three experiments investigate how self-generated explanation influences children's causal learning. Five-yearolds (N = 114) observed data consistent with two hypotheses and were prompted to explain or to report each observation. In Study 1, when making novel generalizations, explainers were more likely to favor the hypothesis that accounted for more observations. In Study 2, explainers favored a hypothesis that was consistent with prior knowledge. Study 3 pitted a hypothesis that accounted for more observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 91 publications
9
55
0
Order By: Relevance
“…In particular, previous research has found that preschoolers who are prompted to explain often show a more sophisticated pattern of responses on later inferences, even when the content of their explanations falls short (Edwards, Williams, Lombrozo, & Gentner, 2016;Walker et al, , 2016Williams & Lombrozo, 2010). Wilkenfeld and Lombrozo (2015) argue that it is the process of explaining that carries epistemic value, regardless of whether it results in the ''correct" product.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, previous research has found that preschoolers who are prompted to explain often show a more sophisticated pattern of responses on later inferences, even when the content of their explanations falls short (Edwards, Williams, Lombrozo, & Gentner, 2016;Walker et al, , 2016Williams & Lombrozo, 2010). Wilkenfeld and Lombrozo (2015) argue that it is the process of explaining that carries epistemic value, regardless of whether it results in the ''correct" product.…”
Section: Resultsmentioning
confidence: 99%
“…Experiment 3 contrasted two conditions in which we asked 3-and 4-year-olds to either report whether the toy activated in each training trial or to explain why the toy did or did not activate in each case. Based on the previous literature reviewed above, we hypothesized that generating an explanation may lead children to consider different hypotheses and, in particular, to search for simpler and more general hypotheses (e.g., Lombrozo, 2012;Walker et al, , 2016Walker, Bonawitz, & Lombrozo, submitted for publication; Williams & Lombrozo, 2013; see also Bonawitz, van Schijndel, Friel, & Schulz, 2012). That might increase the chance that older children will accept the relational hypothesis, even though it has a lower prior probability than the individual hypothesis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…But Douven and Schupbach (2015a) found that, at least in some contexts, Bayes' rule is systematically violated because people's belief updates are influenced by explanatory considerations. These results did not come as a complete surprise, given that previous research had already shown that explanation plays a variety of roles in belief formation and in cognition more generally (Chi, de Leeuw, Chiu, and LaVancher 1994;Legare and Lombrozo 2014;Lombrozo 2006Lombrozo , 2007Lombrozo , 2012Pennington and Hastie 1992; for more recent results, see Walker, Lombrozo, Williams, Rafferty, and Gopnik 2016).…”
Section: Introductionmentioning
confidence: 63%